Approaching mindful multicultural case formulation: Rogers, Yalom, and existential phenomenology. (2nd January 2021) - Felder, Andrew J.; Robbins, Brent D.
ABSTRACT: Narrow or restricted case formulation considerations can limit therapeutic effectiveness, limit the lived base of evidence guiding psychotherapy, and contribute to psychotherapist microaggressions. Notably, Person-Centered Therapy (PCT) and existential phenomenology have, in combination, actively maintained that the cultural landscapes or interconnected world horizons of historical, contextual, and sociocultural matters are inseparable from lived experience. In what can be understood as mindfulness perspectives in their own right, the non-judgmental and presence-centered emphases of PCT and existential phenomenology are suited for mindful and meditative attunement to socioculturally diverse clients. This article sets out to begin providing a basis for person-world centered case formulation themes that are mindfully and meditatively linked with a psychotherapist's depthful ontological attunement and cultural or contextual pan-experiential attunement to clients. These interdependent forms of Humanistic Existential Psychotherapy (HEP) attunement can open onto multiculturally informed person-world centered themes that may contribute to experiential restructuring and sociocultural self-actualization . As a way to enhance HEP's sociocultural sensitivity, existential givens, phenomenological themes, and multicultural worldview values are integratively re-visioned as Sociocultural Lifeworld Themes .